Penggunaan Teknologi Augmented Reality dalam Pembelajaran Tafsir Al-Qur'an pada Lembaga Pendidikan Islam - Yusuf, M. (Academicus: Journal of Teaching and Learning, 2024)
The use of Augmented Reality (AR) technology in teaching the interpretation of the Al-Qur'an in Islamic educational institutions is a profound and relevant issue. Dynamic changes in Islamic teaching approaches drive research on the integration of technology as an effective means to enhance students' understanding and direct involvement in the teaching and learning process. This research adopts a literature review method (library research) with a focus on analyzing scholarly works, books, and articles related to the use of AR in the context of Islamic education. The aim of this research is to explore the potential and positive impact of using AR in enhancing the understanding of the interpretation of the Al-Qur'an. The research findings reveal that the integration of AR in teaching the interpretation of the Al-Qur'an provides a more interactive and profound learning experience. This enables students to connect the sacred text with their real-world context. The success of implementing this technology is reflected in increased student participation, higher learning motivation, and a deeper understanding of the content of the Al-Qur'an interpretation. These findings provide a strong foundation for the development of innovative teaching strategies in Islamic educational institutions, creating a more dynamic and relevant environment for the development of students' religious understanding.